Individual identity, organizational identity and racial transformation in the market research industry in South Africa - Vilakazi, Sibongile Deborah (My University, 2016)
The market research industry prides itself on providing accurate and reliable information and solutions to varying business problems. However, the industry has been faced with the challenge of racial transformation at senior decision-making positions of the organisations. The pace of upward mobility of black researchers is slow and this is a threat for the industry because the senior level positions are often tasked with the analysis of research data and formulation of the strategic insights and business solutions to communicate to clients and stakeholders to meet their business needs. Therefore, it is difficult to be confident that the data about the black market does not get lost in translation and interpretation due to cultural nuances that may not be accessed. What is unique about the market research industry is that promotions to senior level positions are based on training on the job and the mastering of relevant skills on the job rather than specific prior training at college or university level. This opened theoretical and practical questions about the individual and organisational qualities that made it difficult for black researchers to progress to senior level positions. A phenomenological research approach was implemented to explore the lived experiences of the black researchers and the organisations, which could explain the slow upward mobility pace. In-depth semi-structured individual interviews were conducted with four CEOs of prominent organisations in the industry and 14 black researchers at various levels in these organisations. These interviews identified the organisational identity espoused by the leadership and the organisational identity lived by the black researchers. Narrative identity research approach and Erikson’s (1956) stage developmental model guided the process of understanding the individual identity of the black researchers at the point of the interview. The results suggest that there are three categories of black researchers in the industry. It is those who are not promoted within a specified timeframe promised by the leadership who leave the organisations, those who are not promoted but stay in the organisations for longer periods than would have been expected and those researchers who are promoted to senior level positions. Each of these categories shows unique individual qualities that potentially shape their experience in the organisations. A framework for understanding the interplay between the various lived experiences and outcomes has been developed. The slow pace of racial transformation at senior levels of the organisations can be traced to the responses of organisational management to change and the types of social exchange relationships between the black researchers and management. Future research may quantify the findings and validate the framework developed in this study to establish generalisability in the industry and in contexts outside the market research industry. A case study research methodology focusing on all the demographics of the organisations could also enrich the framework.
Thesis (Ph.D.)--University of the Witwatersrand, Faculty of Commerce, Law and Management, Wits Business School, 2016
Keywords: Organizational behavior--South Africa; Blacks--Employment--South Africa; Diversity in the workplace--South Africa; Multiculturalism--South Africa